Characterization and evaluation of stabilized particulate formulations as therapeutic oral vaccines for allergy. (2nd October 2018) - Kaneko, Kan; McDowell, Arlene; Ishii, Yasuyuki; Hook, Sarah
Abstract: Allergic conditions affect more than a quarter of the population in developed countries, but currently available treatments focus more on symptom relief than treating the underlying atopic condition. α-Galactosylceramide (α-GalCer) is a potent immunomodulating compound that has been shown to have a regulatory effect when delivered systemically in nanoparticles. Parenteral delivery is not preferred for chronic conditions, such as allergy, and therefore, the aim of this study was to determine whether a regulatory response could be induced through oral administration in a model of atopy through incorporation of α-GalCer into stable particulate formulations (cationic liposomes, polymerized liposomes and poly(lactic-co-glycolic acid) nanoparticles (PLGA NPs)). The formulations showed only minor changes in particle size, polydispersity index and retention of the model antigen ovalbumin (OVA) during incubation in simulated gastrointestinal (GI) conditions. Oral delivery of α-GalCer in cationic liposomes could induce immunostimulating effects systemically, as seen through increases in serum IgG antibody levels, whereas delivery of α-GalCer in polymerized liposomes and PLGA NPs induced local cytokine changes in the mesenteric lymph nodes (MLNs). The generated responses did not exhibit tolerogenic traits which could be useful for immunoregulation, but the responses generated varied between formulations and suggests that further characterization and optimization could lead to the desired immune response.